Tabu dalam Budaya Banjar : (Analisis Antropologi dan Norma Qur'an) - Rahmat Sholihin; Asmaran Asmaran; Wahyudin Wahyudin; Badrian Badrian; Amelia Rahmaniah (Al-Ulum, 2020)
This paper focuses on the wisdom of Banjar culture, namely pamali. The objectives of this research are first to understand the pamali culture of Banjar, and secondly to see it from the perspective of the Qur'an. The research method used is qualitative research with an anthropological approach. The research locations are in Indonesia, South Kalimantan (Banjarmasin, Martapura, and Amuntai). The findings in this study indicate that the prohibition contained in the Banjar tradition is intended to provide a gentle warning. There are several prohibitions in the Koran regarding culture: do not be disobedient to your parents, teachers, and husbands.